Six Tales from the Age of Generals - Cunha, João Manuel dos Santos (2012)
This essay analyzes six short stories written and published in Brazil during the darkest decade of the military government, the years right after Institutional Act #5 was issued – roughly, the years between 1968 and 1979, which historian Elio Gaspari calls the decade of “unabashed dictatorship” (2002), when institutionalized violence and torture were used by the authoritarian régime as an instrument to repress and exterminate opposition to military rule. Through the analysis of short stories by Flávio Moreira da Costa, Luiz Fernando Emediato and Roberto Drummond, the prevalence of themes related to the political scenario in the production of short fiction in Brazil at that time is made evident, as a fact that contributed to the permanence and renewal of Brazilian literature in that period.